Extraction, Chemical Composition and Antidiabetic Potential of Crude Polysaccharides from Centella asiatica (L.) Urban - Meng Li; Muhammad Shahid; Xiaobin Zhang; Douglas Law; Mukram Muhammad Mackeen; Arnida Hani Teh; Ahmad Abdul Kareem Najm; Shazrul Fazry; Babul Airianah Othman (Polish Journal of Food and Nutrition Sciences)
The global prevalence of diabetes mellitus (DM) is escalating, posing a significant challenge to human healthcare systems. In the present study, mineral and monosaccharide compositions, and antidiabetic potential of polysaccharide fractions separated from Centella asiatica (L.) leaves (CAL) were assessed. Initial single-factor experiments identified key extraction parameters, further optimized through response surface methodology (RSM) with optimal conditions determined as a liquid-to-solid ratio of 24.43:1 (mL/g), extraction time of 60.76 min, and a temperature of 83.31℃. Alcohol insoluble residue (AIR) extraction yielded three crude polysaccharide fractions (P50, P70, and P90). P50 was obtained with the highest yield (14.31%) and exhibited the highest content of total sugars and uronic acids (68.01 and 24.28 g/100 g, respectively). Calcium, magnesium, and manganese were dominant minerals in P50 and P70. Monosaccharide composition analysis via high-performance liquid chromatography (HPLC) demonstrated enrichment of galacturonic acid, galactose, and arabinose in P50 and P70. Furthermore, both fractions (P50 and P70) exhibited dose-dependent inhibitory effects on α-amylase and α-glucosidase. At 5 mg/mL, P50 caused 68.3% α-amylase inhibition and 62.3% α-glucosidase inhibition, while P70 triggered 46.8% and 34.1% inhibition, respectively. In conclusion, this study is the first to provide valuable insights into optimizing CAL extraction conditions. Potential utilization of polysaccharide fractions obtained from CAL as components for formulating functional foods can be explored in the future.